1997
DOI: 10.1097/00005537-199710000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Objective Measures for Facial Paralysis

Abstract: A shift from subjective scales to objective measures of facial paralysis requires physical models against which to validate and calibrate the new objective techniques. The purpose of this report was to demonstrate such a model and to test the capacity of an objective computer system to accurately measure physical change. The physical model consisted of an advancing edge of a spreading gelatin film. The model was measured in submillimeter increments. Concurrent measurements were made using the computed system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The light reflectance was taken as a two‐dimensional marker of the three‐dimensional surface deformation occurring during facial expression. Helling and Neely 25 studied the proprietary Neely‐Cheung Facial Analysis Computerized Evaluation (FACE) System against a physical model consisting of the advancing edge of a spreading gelatin film. They demonstrated that their objective system (FACE) for the measurement of degrees of paresis and synkinesis was highly correlated with minute increments of movement of the physical model.…”
Section: Introductionmentioning
confidence: 99%
“…The light reflectance was taken as a two‐dimensional marker of the three‐dimensional surface deformation occurring during facial expression. Helling and Neely 25 studied the proprietary Neely‐Cheung Facial Analysis Computerized Evaluation (FACE) System against a physical model consisting of the advancing edge of a spreading gelatin film. They demonstrated that their objective system (FACE) for the measurement of degrees of paresis and synkinesis was highly correlated with minute increments of movement of the physical model.…”
Section: Introductionmentioning
confidence: 99%
“…The Neely-Cheung Facial Analysis Computerized Evaluation (FACE) system 21,[37][38][39] and objective scaling of facial nerve function based on area analysis (OSCAR) 40 provide direct measures of facial contour changes based on changes in light reflectance but require head fixation and yield no information about direction or magnitude of motion. The Vicon Motion system, 41 Peak Motus Motions System, 42 Motion Analysis system, [43][44][45][46] and Expert Vision Motion Analysis System 47 all use automated tracking of reflective markers affixed to the face to quantify displacement, speed, acceleration, and direction of motion in 3 dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…We measured synkinesis with a landmark‐based video and computer system, an accepted, reliable, and valid way of measuring facial motion. Several other investigators have used similar techniques for measurement of facial motion in paralyzed and synkinetic faces 3–6 …”
Section: Dear Editormentioning
confidence: 99%